Partial Oral versus Intravenous Antibiotic Treatment of Endocarditis - Iversen, Kasper; Ihlemann, Nikolaj; Gill, Sabine U; Madsen, Trine; Elming, Hanne; Jensen, Kaare T; Bruun, Niels E; Høfsten, Dan E; Fursted, Kurt; Christensen, Jens J; Schultz, Martin; Klein, Christine F; et al. (The New England journal of medicine, 2019)
In this randomized, controlled trial conducted at Danish cardiac centers, intravenous antibiotic therapy was compared with partial oral antibiotic therapy for the treatment of bacterial endocarditis. The outcomes were similar in the two groups.